PERILAKU PETANI PADI DALAM MENGIMPLEMENTASIKAN PENGENDALIAN HAMA TERPADU (PHT) MENGGUNAKAN TANAMAN REFUGIA - Ghigga Mughyi Maghfirillah; Oeng Anwarudin; Nazaruddin Nazaruddin (Jurnal Inovasi Penelitian, 2020)
The low productivity of rice in Cisitu Subdistrict uses Integrated Pest Management (IPM) technology in rice cultivation that is not yet optimal. Planting refugia as a side crop can encourage the conservation of natural enemies such as predators. This study aims to describe the policy of farmers in implementing refugia plants, analyze the factors related to the application of refugia plants, and formulate strategies to improve the protection of farmers in implementing refugia plants. The research was conducted in Cisitu Subdistrict, Sumedang Regency in April to June 2020. Responding to the study of 45 people who were determined by census techniques with all the number of participants participating in the research. The research variables consisted of the characteristics of respondents, extension activities, the function of farmer groups, and implementation of refugia plants. Analysis of the data used is descriptive analysis, Spearman Rank correlation analysis and variable ranking. The results of research involving the implementation of integrated pests using refugia plants are included in the medium category with a presentation of 86.70%. Factors governing the implementation of integrated controls using refugia are large areas, extension activities, innovation, the role of extension workers, a vehicle for cooperation, and production units. Strategies in an effort to improve the implementation of integrated pest control using refugia crops are to increase the effectiveness of land use, increase the role of agricultural extension workers, strengthen farmer working groups as a vehicle for cooperation and production units, increase encouraging activities, and choose ways to support materials that support farmers' needs, easily applied, cheap and felt the benefits.